Analisis Spasial Unsur Pariwisata Sejarah Budaya di Kabupaten Sumenep untuk Pembangunan Pariwisata dalam Meningkatkan Perekonomian Daerah - Yuda, Mas Rangga; Sulistiyo, Wahyu Djoko (Jurnal Master Pariwisata (JUMPA); Volume 08, Nomor 02, Januari 2022, 2022)
The Sumenep Regency Government since 2018 has planned to make Sumenep a tourism city. This is stated in the Sumenep Regency Government program called "Visit Sumenep 2018". As a region, tourism and culture play a major role in it, but the existing distribution of cultural tourism still has many shortcomings. This will certainly have an impact on the existence of historical cultural sites, visitor comfort and the economy of the community. The purpose of this study was to determine the strategic area of historical tourism in Sumenep Regency with 4A elements of culture (Attractions, Amenities, Accessibility and Ancilliary). The method used in this study is spatial analysis with consideration of 4A as a tourism supporter. The results of this study indicate that Sumenep Regency is a strategic area characterized by the interaction between 4A tourism and the distribution of historical and cultural tourism sites. Keywords: Spatial Analysis, Cultural History Tourism Site, Element 4A.